Management of massive pulmonary embolism after jejuno-ileal bypass for morbid obesity - Rao, Gopal (1981)
Four patients developed massive pulmonary embolism after jejuno-ileal bypass for morbid obesity. All patients were in Greenfield's Class IV and were in shock. Severe hypoxia was evidenced in their blood gases. The patients were managed with digitalis, diuretics, Solu-Medrol (methylprednisolone sodium succinate), oxygen, and heparin therapy. Each patient underwent partial vena cava interruption with Mobin Uddin's umbrella, and all four survived without residual complications.